2011
DOI: 10.1080/02508281.2011.11081661
|View full text |Cite
|
Sign up to set email alerts
|

Volunteer Tourism: As Good as It Seems?

Abstract: I Research Probe I This Department has been specifically created to include findings of special significance and problem areas of subtle nuances in tourism research. Insightful contributions presenting the state-of-the-art, preferably from the developing societies, will be appreciated. It will also encourage scholars and authors to think against the grain, probing the consistency of theoretical notions and research trends whose heuristic value is all too often taken for granted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 43 publications
1
34
0
1
Order By: Relevance
“…Having achieved intercultural sensitivity beyond appreciation of cultural difference, these individuals could act as ambassadors for cross-cultural understanding throughout the world. Interestingly, the results indicated that duration and the community nature of volunteer work were also associated with negative changes at the defense stage of intercultural sensitivity development, supporting Guttentag's (2009Guttentag's ( , 2011 and Sin's (2010) assertions that volunteer tourism may reinforce negative stereotypes and thus facilitate crosscultural misunderstanding. Volunteer tourists with this orientation take pride in their own culture and tend to see it as a goal for the entire world.…”
Section: Duration Type Of Program and Intercultural Sensitivitysupporting
confidence: 56%
See 2 more Smart Citations
“…Having achieved intercultural sensitivity beyond appreciation of cultural difference, these individuals could act as ambassadors for cross-cultural understanding throughout the world. Interestingly, the results indicated that duration and the community nature of volunteer work were also associated with negative changes at the defense stage of intercultural sensitivity development, supporting Guttentag's (2009Guttentag's ( , 2011 and Sin's (2010) assertions that volunteer tourism may reinforce negative stereotypes and thus facilitate crosscultural misunderstanding. Volunteer tourists with this orientation take pride in their own culture and tend to see it as a goal for the entire world.…”
Section: Duration Type Of Program and Intercultural Sensitivitysupporting
confidence: 56%
“…Applying this approach to the issue of cross-cultural understanding, it is evident that proponents (advocacy platform) see volunteer tourism as promoting mutually beneficial relationships between tourists and host communities and thus facilitating cross-cultural understanding (Vodopivec & Jaffe, 2011;Wearing, 2001). Critics (cautionary platform), however, posit that volunteer tourism may promote rationalization of poverty, initiate undesirable cultural changes within host communities, and result in cross-cultural misunderstanding due to the lack of close and informative interaction (Guttentag, 2009(Guttentag, , 2011Sin, 2010). Other researchers (e.g.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Similarly, due to the great variety of volunteer tourism experiences on offer, the industry has become 'increasingly ambiguous in definition and context' (Callanan & Thomas, 2005:195). This is coupled with the rapid expansion and commercialisation of the voluntourism sector (Butcher, 2011;Guttentag, 2011;Raymond, 2011).…”
Section: Voluntourismmentioning
confidence: 99%
“…However, the volunteer tourism marketplace is ever evolving and in recent years we have seen new businesses entering the market. A significant increase in the number of commercial operators has changed the face of the industry and the discussion about real benefits of volunteer tourism have appeared (e.g., [23][24][25][26][27]). These profit-oriented organizations have usually the opposite impact on communities than non-profit organizations [14].…”
Section: Literature Reviewmentioning
confidence: 99%